Insectos comestibles del Estado de México y determinación de su valor nutritivo - RAMOS ELORDUY, JULIETA; PINO MORENO, JOSÉ MANUEL (Anales del Instituto de Biología serie Zoología, 2009)
IS THE STATE OF MEXICO WE RECORDED 104 SPECIES OF EDIBLE INCECTS SPECIES, INCLUDED IN TEN ORDERS OF THE INSECTA CLASS, THE MOST CONSUMED BELONGING TO HYMENOPTERA, ORTHOPTERA, HEMIPTERA AND COLEOPTERA. THE MAJORITY OF THE SPECIES WERE ANALYZED IN ORDER TO KNOW THEIR NUTRITIVE VALUE, MAKING EMPHASIS IN THEIR PROTEIN CONTENT. THE PERSENTAGE OF PROTEINS VARIES FROM 9.45 TO 77.13% CORRESPONDING TO MYMECOSISTUS MELLIGER (HYMENOPTERA-FORMICIDAE) AND TO MELANOPLUS MEXICANUS (ORTHOPTERA-ACRIDIDAE), RESPECTIVELY. WE ALSO DISCUSS THEIR PROTEIN QUALITY COMPARING THE VALUES OBTAIBNED AGAINST THE FAO/WHO/UNU, 1985 PATTERN, THEIR DIGESTIBILITY, AND THE QUANTITY OF B GROUP VITAMINS, MINERAL SALTS AND ENERGY THAT THEY SUPPLY TO THE DIET OF DIFFERENT ETHNIC GROUPS SETTLED THERE.